Homicidal Strangulation: The Leading Cause in All Asphyxial Deaths in Allama Iqbal Medical College, Lahore during the Year 2013 (Medical Forum Monthly, 2024)
Objective: The objective of this study was to find out the commonest cause of death in these asphyxial deaths during the period of study and to compare it with other studies previously carried out on this subject.Study Design: Observational / descriptive study.Place and Duration of Study: This study was conducted at Forensic Medicine Department AIMC, Lahore from January 2013 to December 2013.Materials and Methods: Total medico-legal autopsies were 221. Out of these 32 were the cases of mechanical asphyxial deaths, which were selected for this study. The documents scrutinized for this purpose was, autopsy reports, police papers and hospital charts.Results: Out of all post-mortems conducted, the mechanical asphyxial deaths were 32 (14.47%). Amongst them the cases of strangulations were the most 16 (50%), next in number were the cases of drowning 8 (25%). There were 6 (18.75%) cases of throttling, and only 2 (6.25%) cases were of hanging. None of them was the case of traumatic asphyxia. In 32 cases of all asphyxial deaths males were 17(53.12%). Amongst these 16 cases of strangulation the 3rdand 4th decades showed higher incidence. In all asphyxial deaths male (17) and females (15) show almost equal distribution. Strangulation is the most prevalent cause of death in all 32 asphyxial deaths. Almost all strangulation deaths were homicidal and hanging was suicidal. Similarly all throttling cases were homicidal. Ligature strangulation and throttling were the methods used in homicidal manner (50.00%) while hanging was used for suicide (6.25%). In hanging the position of the knot was at occiput in all cases. In ligature strangulation showed the knot on the front in almost all cases.Conclusion: Amongst all asphyxial deaths the most prevalent cause was strangulation and manner in all was homicidal, it is one of the commonest causes of deaths in our country. So strangulation remains the most preferred method of homicidal asphyxial killings.